(3Jcejd RgQ GdQjGV (B( (3aj JQLeI GdbGVi YjGV (B)s - (3eMeO Hf YHO Gddg GdbfWQj GdbUQj, CHh YHO Gddgs
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf LGHQ GdhGOi BTi gh GdEeGe GdbGVi CHh GdaVd YjGV Hf ehSi s
(3BNQgG (B:s
(3dG eYbH dMceg , hdG QGO dbVGFg ai SGHb Ydeg GfJgi s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(28 / 2) s
Keywords: (3GdJGQjNs